CHARACTER ANALYSIS IN ACHILLEA SECT. SANTOLINOIDEA (COMPOSITAE–ANTHEMIDEAE): PART I. LEAF AND FLORAL MORPHOLOGY - VALANT-VETSCHERA, K. M.; KÄSTNER, A. (Edinburgh Journal of Botany, 2000)
Twenty-two species of Achillea sect. Santolinoidea (DC.) O. Hoffm., as currently understood, were analysed morphologically. Emphasis was put on clear definitions of characters and their states as were deduced from detailed graphical analysis. Major character sets include details of leaf structure and differentiation of leaflet lobes as well as of floral characters (form of flower heads, ligules, phyllaries, bracts). Character descriptions were compared with floristic literature and original diagnoses, but little consistency was observed in the applied terminology. There is little indication of unifying character states for sect. Santolinoidea, as a result of low frequencies of occurrence, although the section appears to be uniform on the basis of the general leaf structure. However, species-specificity of some character states (leaves, bracts, phyllaries) was observed that might prove useful for species delimitation.